THE EFFECT OF SIMULATION METHOD EDUCATION ON EARTHQUAKE DISASTER PREPAREDNESS AT SMP NEGERI 7 PALU: PENGARUH PENDIDIKAN METODE SIMULASI TERHADAP KESIAPSIAGAAN BENCANA GEMPA BUMI DI SMP NEGERI 7 PALU - Hasnidar, Hasnidar; Sukrang; Parmin; Fauzan; Ni Wayan Sridani; Nur Indang (Universitas Islam Negeri Alauddin Makassar, 2025)
Central Sulawesi lies within a seismically active region, particularly along subduction zones and fault lines that extend across both marine and terrestrial domains. This area has experienced several major earthquakes, resulting in substantial physical destruction, human casualties, and profound socio-economic repercussions. Consequently, targeted educational initiatives are essential to enhance community resilience and preparedness. Among various approaches, simulation-based training stands out as an effective strategy, offering participants hands-on experience in managing emergency scenarios. This study aimed to evaluate the impact of simulation-based education on earthquake disaster preparedness among adolescents.Employing a quasi-experimental design with a non-equivalent control group approach, the research involved 45 participants in the intervention group and 45 in the control group. Data analysis utilized the Wilcoxon signed-rank test for within-group comparisons and the Mann-Whitney U test for between-group differences, with statistical significance set at p < 0.05. The Mann-Whitney U test on pre-intervention data yielded a p-value of 0.267 (p > 0.05), indicating no significant difference in baseline earthquake preparedness between the groups. In contrast, post-intervention analysis revealed a p-value of 0.000 (p < 0.05), demonstrating a statistically significant divergence in preparedness levels between the intervention and control groups.These findings suggest that simulation-based education positively influences earthquake preparedness among adolescents at SMP Negeri 7 Palu. It is anticipated that such interventions will bolster students' knowledge, attitudes, and practical behaviors toward earthquake mitigation, thereby improving their capacity for self-rescue during seismic events.